Multiliteracies: A Promising Method of EFL Classrooms in Thailand - Chanyoo, Natthapong (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University, 2017)
The term multiliteracies has been coined by a group of scholars who realized importance of the fast change of technology, increasing people’s awareness of cultural diversity, and global connectedness that would change the way people communicate. The change influences the evolving nature of texts and messages that are presented through different channels. As a result, a pedagogy of multiliteracies required different way of thinking about texts and assessment (Jacobs, 2013, p. 623). As English is a prevailing means for global communication, and is presented through different kinds of channels, modes, and media, English language teachers and learners are required to possess three multiliterate skills: proficiency of the language, awareness of global diversity, and interpretation of meaning from multimodal texts. This paper aims to address (1) how multiliteracies pedagogy influences learning and instruction in the 21st century, especially in the English language classrooms, and (2) to discuss the plausibility in incorporating multiliteracies in the Thai EFL classrooms. The paper gives an insight of how EFL teachers in Thailand should be informed about the evolving nature of meaning-making of the texts of English in different forms and channels. Keywords: multiliteracies, English as a foreign language, Thailand